The hanging : a thriller - Hammer, Lotte (Hammer, Lotte. Konrad Simonsen series., 2013)
"One morning before school, two children find the naked bodies of five men hanging from the gym ceiling. The case leads detective Konrad Simonsen and his murder squad to the school janitor, who may know more about the killings than he is telling. Soon, Simonsen realizes that each of the five murdered men had a dark and terrible secret in common. And when Simonsen's own daughter is targeted, he must race to find the culprit before his whole world is destroyed."--Provided by publisher.